2020
DOI: 10.1007/s12035-020-01908-3
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod Affects Transcription of Genes Encoding Enzymes of Ceramide Metabolism in Animal Model of Alzheimer’s Disease

Abstract: The imbalance in sphingolipid signaling may be critically linked to the upstream events in the neurodegenerative cascade of Alzheimer's disease (AD). We analyzed the influence of mutant (V717I) amyloid β precursor protein (AβPP) transgene on sphingolipid metabolism enzymes in mouse hippocampus. At 3 months of age AβPP/Aβ presence upregulated enzymes of ceramide turnover on the salvage pathway: ceramide synthases (CERS2, CERS4, CERS6) and also ceramidase ACER3. At 6 months, only CERS6 was elevated, and no ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…Because sphingomyelin and sphingolipid signaling activate the pro-survival S1P-S1P receptor pathway [ 23 ], we next investigated if sphingomyelin and S1P synthesis in acid-induced OS spheroids was able to modulate cell viability. To this aim, we used myriocin, an inhibitor of serine palmitoyltransferase (SPT) [ 52 ], and its derivative FTY720 (Fingolimod), which inhibits G protein-coupled S1P receptors and blocks oncogenic signaling [ 53 , 54 , 55 , 56 ]. Both myriocin and FTY720 were able to impair S1P accumulation in 143B spheroids under acidity, with a greater effect shown by FTY720 ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because sphingomyelin and sphingolipid signaling activate the pro-survival S1P-S1P receptor pathway [ 23 ], we next investigated if sphingomyelin and S1P synthesis in acid-induced OS spheroids was able to modulate cell viability. To this aim, we used myriocin, an inhibitor of serine palmitoyltransferase (SPT) [ 52 ], and its derivative FTY720 (Fingolimod), which inhibits G protein-coupled S1P receptors and blocks oncogenic signaling [ 53 , 54 , 55 , 56 ]. Both myriocin and FTY720 were able to impair S1P accumulation in 143B spheroids under acidity, with a greater effect shown by FTY720 ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 99%
“…FTY720 has several anticancer effects [ 77 , 78 , 79 , 80 , 81 ] but its activity in OS has not been explored so far. Despite being considered an S1P receptor modulator, FTY720 is also able to induce changes in the enzymes of the sphingolipid pathway, including SPHK1 [ 54 , 55 , 56 ], thus providing an explanation for the reduction of S1P seen in our model. FTY720 inhibited LD and S1P accumulation in acid-treated spheroids, and, as a consequence, impaired cell survival and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation is linked to familial FAD/early onset AD and stimulates the production of Aβ, especially its most toxic 42 amino acid species. Despite obvious limitations shared with other animal models of AD, the mice display a temporal sequence of behavioral alterations characteristic for AD and relatively closely follow disturbances of sphingolipid metabolism we noted in the human brain (Moechars et al, 1999;Van Dorpe et al, 2000;Jeśko et al, 2019bJeśko et al, , 2020.…”
Section: Resultsmentioning
confidence: 72%
“…Our previous analysis (Jeśko et al, 2019b(Jeśko et al, , 2020 has shown that the reaction of mouse brain to the expression of AβPP (V717I) transgene is highly different at various ages. The presence of AβPP in adult (3-month-old) animals was associated with elevated ceramide turnover (higher expression of both ceramide-synthesizing and -degrading enzymes of the salvage pathway of sphingolipid metabolism), but 12-month-old transgenic mice only displayed a reduction in the expression of ceramide-utilizing enzymes in the sphingomyelinase pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation